Corporate environmental impact - Park, D. G.,Freiberg, David,Serafeim, George,Zochowski, Rob (Harvard Business School, 2020)
As an organization’s environmental impact has become a central societal consideration, thereby affecting industry and organizational competitiveness, interest in measuring and analyzing environmental impact has increased. We develop a methodology to derive comparable and scalable monetized environmental impact estimates by applying characterization pathways and monetization factors to organization level environmental outputs, including carbon emissions, water use, and other emission types. The median environmental impact as a percentage of an organization’s sales (operating income), referred to as environmental intensity, is 2% (22%) suggesting a significant level of ‘hidden liabilities’ and potential for value erosion if environmental impacts are priced. About 60% of the variation in environmental intensity is driven by industry membership, while the rest can be attributed to firm specific factors or to country and more granular industry classifications. Environmental intensity exhibits moderate correlation with various environmental ratings across firms and industries and no correlation across firms within industries. Firms with higher environmental intensity exhibit lower corporate market valuation, consistent with investors viewing environmental impacts as financially material and pricing them in some but not all industries. We document the dynamic materiality of environmental intensity, where the relation between environmental intensity and corporation valuation has become stronger in recent years
10.2139/ssrn.3565533
Keywords: Graue Literatur; environment; impact; measurement; ratings; valuation